Identificación taxonómica de especies forestales de la familia Anacardiaceae del arboretum "El Huayo" Puerto Almendras, Loreto-Perú 2021 - Aguilar del Castillo, Miguel David (2022)
This research work has been carried out in the Arboretum el Huayo of the Forestry Research and Education Center in Puerto Almendra, FCF-UNAP. Its objective was to taxonomically identify the forest species belonging to the Anacardiaceae family with diameter at breast height (DBH ? 10 cm) and determine the number of individuals that constitute the population in the permanent sampling plots (PPM) of the Arboretum "El Huayo”. The methodology applied was that of the inventory describing and interpreting what exists in the varillal-type forest fragment of the "the Huayo" arboretum; The population was made up of all the forest species that make up the Anacardiácea family with a diameter ? 10 cm. The results contribute to the identification in terms of genus and species of the family Anacardiaceae Tapirira, retusa Ducke, Tapirira guianensis Aubl, Tapirira obtusa (Beth) J.D. Mitck and Anacardium giganteum Hancock ex Engl. 143 individuals of Tapirira retusa Ducke have been found, representing 50.89 percent of the total 281 individuals of the anacardiaceae family. The Tapirira guianensis Aubl with 134 individuals representing 47.69 percent of 281 individuals of the anacardiaceae family. The species Tapirira obtusa (Beth) J.D Mitch and Anacardium giganteum Hancock ex Engl. They are the ones with the least population with 3 individuals and 1 individual representing 1.07% and 0.36% of the total population of the arboretum.